Juvenile Behсet's Disease: Clinical Observation - Nikolai V. Sobotiuk; Alexei V. Kononov; Sergei V. Bochantsev; Svetlana A. Golochalova; Lidia V. Makarova; Lusine A. Ustian; Tatiana G. Pertels; Yevgenia E. Shlykova; Tatiana F. Pogodaeva ("Paediatrician" Publishers LLC, 2016)
Behcet's disease is a type of systemic vasculitis of unknown etiology characterized by recurrent erosive and ulcerative lesions of the mucous membrane in the mouth and genitals and pathological processes in the joints, central nervous system, and gastrointestinal tract. Polysystemic clinical manifestations, relatively rare occurrence, especially in childhood, and absence of pathognomonic laboratory signs make this disease difficult to verify. The diagnosis of Behcet's disease is especially complicated in cases where the intestinal symptoms are presented as initial or predominant manifestations of the disease, because they are often erroneously regarded as inflammatory bowel diseases. It should be added that the diagnosis of Behcet's disease is based on a set of classification/diagnostic signs that can develop for 5-6 years or more. The article presents a case of juvenile Behcet's disease demonstrating the complexity of the search for diagnosis. A brief literature review discusses the current view on the problem of diagnosis, pathogenesis, clinical presentation, and treatment of the disease in pediatric practice.